Model Simulasi PertumbuhanTanaman Jagung Manis Hibrida pada Jarak Tanam yang Berbeda - Ervan Ferdiansyah; Handoko Handoko; Impron Impron (Institut Pertanian Bogor, 2020)
A sweet corn model was developed to simulate the growth and development of hybrid-sweet corn under different crop denssities. This research is comparing the data of the simulation model and the actual observation data in the field, which is then presented in graphical form. This model was conducted on six treatment combinations between three types of spacing and two varieties. The simulation model requires meteorological data (average temperature, humidity, precipitation, and radiation), soil water data, and crop chracteristics. There are five of the six plant combinations which graph show that the model is able to simulate the total maize corn biomass every week. The model was able to estimate 93% of the actual biomass and described the growth and development of hybrid-sweet corn as well. Keywords: estimating biomass, models and simulations, plant growth